Pengaruh Laba Akuntansi dan Arus Kas Operasi terhadap Return Saham - Aida Listianti; Sudradjat Sudradjat (Indonesian Accounting Literacy Journal, 2020)
An investor in investing always expects high stock returns. Therefore, investors must be able to assess which companies have a good performance, so their stock returns are also high. One of the important information that can be used by investors to assess the company’s financial performance is financial reports, especially those related to accounting profit and operating cash flow. The purpose of this study was to analyze the effect of accounting profit and operating cash flow on stock return. The method used to select the sample in this study was purposive sampling. This study uses multiple linear regression analysis. Based on the result of this study, partially (t test) the accounting profit variable effects stock returns while operating cash flow has no effect on stock returns. Simultaneously (f test) variable accounting profit and operating cash flow have an effect on stuck returns.